2016
DOI: 10.1111/oik.02372
|View full text |Cite
|
Sign up to set email alerts
|

How much do phenotypic plasticity and local genetic variation contribute to phenotypic divergences along environmental gradients in widespread invasive plants? A meta‐analysis

Abstract: For introduced species that have spread across a wide distributional range, phenotypic plasticity (PLA) has often been proposed as an important contributor to invasion success, because it increases the survival rate during initial colonization. In contrast, local genetic variation (LOC) has also been proposed to be important, because it could allow invaders to evolve high performance in a new habitat. While evolutionary ecologists have long been interested in understanding genetic mechanisms that allow rapid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 114 publications
(120 reference statements)
5
52
0
Order By: Relevance
“…Similarly, trait plasticity may enhance competitive responses if species can shift their root traits to avoid competition belowground or their leaf traits to competitively suppress their neighbors (Bennett, Riibak, Tamme, et al., ). Similar effects of trait plasticity can also affect biotic resistance experienced by invaders (Conti et al., ), although its importance may depend on the characteristics of the invading species (Liao et al., ) and the traits that exhibit plasticity (Godoy, Valladares, & Castro‐Díez, ). Regardless of its importance, incorporating trait plasticity in similarity–invasion models will likely remain challenging unless plasticity is treated as a trait.…”
Section: Intraspecific Trait Variation and Phenotypic Plasticitymentioning
confidence: 99%
“…Similarly, trait plasticity may enhance competitive responses if species can shift their root traits to avoid competition belowground or their leaf traits to competitively suppress their neighbors (Bennett, Riibak, Tamme, et al., ). Similar effects of trait plasticity can also affect biotic resistance experienced by invaders (Conti et al., ), although its importance may depend on the characteristics of the invading species (Liao et al., ) and the traits that exhibit plasticity (Godoy, Valladares, & Castro‐Díez, ). Regardless of its importance, incorporating trait plasticity in similarity–invasion models will likely remain challenging unless plasticity is treated as a trait.…”
Section: Intraspecific Trait Variation and Phenotypic Plasticitymentioning
confidence: 99%
“…However, the incidences of exotic plants invading some rarely inhabited, stressful habitats have increased dramatically (Caño, Mendizabal, Baquero, & Herrera, ). The greater expansion potential of invasive compared with native species is often attributed to fast adaptive responses to stresses (Liao, D'Antonio, Chen, Huang, & Peng, ). Plants might evolve a stronger tolerance to one stressor in order to persist in a particular habitat (Ahmad, Ashraf, & Ali, ), and such evolution has been proposed to incur costs on plant performance (Bijlsma & Loeschcke, ; Lachmuth, Durka, & Schurr, ) and affect the responses to other stressors (Brenes‐Arguedas, Roddy, & Kursar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high plasticity levels are not necessarily associated with fitness gains (Davidson et al., 2011) and reaching a particular balance between plasticity and local trait adaptation could be key to invasive success (Liao, D'Antonio, Chen, Huang, & Peng, 2016). Rapid local adaptation by colonizing or invading species is an alternative to phenotypic plasticity for coping with new environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that local adaptation might be a more common response to variable environments than adaptive phenotypic plasticity (Palacio‐López, Beckage, Scheiner, & Molofsky, 2015). A second meta‐analysis (Liao et al., 2016) suggested that phenotypic plasticity explained a higher proportion of phenotypic variation in clonal, self‐compatible, and perennial species, whereas local adaptation explained more phenotypic variation for annual species. Liao et al.…”
Section: Introductionmentioning
confidence: 99%